Phase and optical behaviours of chiral-azo liquid crystal polymethylsiloxanes with isosorbide units. Issue 5 (8th April 2020) - Ma, Ya-ru; He, Xiao-Zhi; Cong, Yue-Hua; Zhang, Bao-Yan; Liu, Ze-Ping; Wang, Ji-Wei; Jia, Ying-gang
ABSTRACT: In this study, we synthesised two series of cholesteric liquid crystal polymers CPQ and CPZ series. First, we prepared four different monomers ML1 containing a cholesteryl group, ML2 containing a cyano group, ML3 containing a phenolic hydroxyl group and ML4 containing isosorbide with azo groups. With the polymethylsiloxanes as the main chain, CPQ series were then synthesised by copolymerisation among the monomers ML1, ML2 and ML3 and CPZ series were synthesised by esterification between the CPQ series and the monomer ML4 . 1 HNMR and FT-IR spectra confirmed the chemical structures of all the monomers and polymers. The mesomorphic behaviours and thermal properties were investigated by TGA, DSC, POM and XRD. Both the CPQ and CPZ series exhibited excellent thermal stability and reversible phase transitions, as well as interesting Grandjean textures under POM. CPZ series showed higher optical activity than CPQ series due to the introduction of the isosorbide group and the azo group, which could tune the pitch to make Bragg selective reflection appear more easily. UV–Vis spectra investigated the photoresponse behaviours of CPZ series thoroughly. Graphical Abstract: